Spongecake and eggroll: two hereditary diseases in Drosophila resemble patterns of human brain degeneration. - Min, K.T.; Benzer, S. (Current Biology, 1997)
Various neuronal degenerative diseases are characterized by late onset, relentless progression, and finally death. Many have a direct genetic basis; others are of still unknown etiological mechanisms [1,2]. The study of human neurodegenerative diseases is complicated by the difficulty of obtaining tissue samples at various stages of progression, especially early in the course of the disease. Since neurodegeneration occurs in many organisms [3-5], model organisms amenable to genetic and molecular techniques, such as the mouse, offer important advantages. Much less laborious and expensive are worms or flies, which have short generation times and can be rapidly screened for mutations. To investigate the use of the fly as a model system for identifying genes related to such diseases, we screened for mutants having reduced lifespan, then examined them for brain degeneration. We describe here two such mutants, each with a different pattern of degeneration as characterized by light and transmission electron microscopy. The brain of the aging spongecake mutant exhibits regionally specific, membrane-bound vacuoles similar to those seen in spongiform degenerations such as Creutzfeldt-Jakob disease [6,7]. The mutant eggroll develops dense, multilamellated structures in the brain, resembling ones found in lipid storage diseases such as Tay-Sachs [8].